Un año y medio de Estatuto del Trabajo Autónomo y su infradesarrollo: y en eso llegó una gran crisis económica - López i Mora, Frederic (REVESCO. Revista de Estudios Cooperativos, 2009)
The autonomous work has a notable implantation in Spain and fulfills a relatively wide functionality in our economic and social system. In the set of the managerial, there is absolutely hegemonic the figure of the autonomous one who has not wage earners to his service, together with that it uses up to two workpeople for foreign account. Before the parliamentary approval of the Law 20/2007, his regulation was turning out to be very fragmentary, deficient and obsolete, without attending on the deep transformations that have happened after the arrival of the posfordism to this sector. With the coming into effect of the above mentioned norm, Spain has a law - frame, pioneer in the European Union and surely in the world, which establishes a juridical minimal pattern, common and unrepealable for all the autonomous ones that produce in our country. This study, fundamentally juridical, does not center on the analysis of the said disposition – baptized as Statute of the Autonomous Work-, but on his later development from his approval on July 12, 2007 until ends of the year 2008; but, in view of that this process has come to coincide with a deep economic crisis, the investigation complements itself with a critical note on the principal measurements of shock adopted by public power to confront the impact of the recession on the autonomous workpeople, to close with a reflection on the structural implications and challenges that supposes the above mentioned Statute, both in Spain and in the bosom of the European Union.
Keywords: Independent worker; Professional Statute; Functionality; Economic crisis; Measurements; Social Economy